2006
DOI: 10.1073/pnas.0600863103
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase DZ2 plays an important role in extraplastidic galactolipid biosynthesis and phosphate recycling in Arabidopsis roots

Abstract: Low phosphate (Pi) availability is one of the major constraints for plant productivity in natural and agricultural ecosystems. Plants have evolved a myriad of developmental and biochemical mechanisms to increase internal Pi uptake and utilization efficiency. One important biochemical pathway leading to an increase in internal Pi availability is the hydrolysis of phospholipids. Hydrolyzed phospholipids are replaced by nonphosphorus lipids such as galactolipids and sulfolipids, which help to maintain the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
238
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(246 citation statements)
references
References 34 publications
7
238
1
Order By: Relevance
“…In addition, the PLDz1 and z2 double knockout displayed shorter primary roots and had a lower concentration of PA in roots than wildtype plants under the same phosphorus-limited conditions. Another study showed that PLDz2 was involved in lipid turnover in a phosphorus-limited condition (Cruz-Ramirez et al, 2006). These results suggest that PLDz1 and z2 play a role in regulating root development in response to phosphorus limitation, but their roles, especially their potential additive roles, in the turnover of phospholipids and galactolipid accumulation during phosphorus starvation have not been investigated prior to this study (to our knowledge).…”
mentioning
confidence: 71%
“…In addition, the PLDz1 and z2 double knockout displayed shorter primary roots and had a lower concentration of PA in roots than wildtype plants under the same phosphorus-limited conditions. Another study showed that PLDz2 was involved in lipid turnover in a phosphorus-limited condition (Cruz-Ramirez et al, 2006). These results suggest that PLDz1 and z2 play a role in regulating root development in response to phosphorus limitation, but their roles, especially their potential additive roles, in the turnover of phospholipids and galactolipid accumulation during phosphorus starvation have not been investigated prior to this study (to our knowledge).…”
mentioning
confidence: 71%
“…In contrast, PLD derived PA in animals has been reported to be dephosphorylated by lipid phosphate phosphatases to yield DAG (Pyne, et al, 2005). An intriguing exemption is the proposed function of the ζ-class (PX-PH) PLDs in the plant response to phosphate starvation (Cruz-Ramirez et al, 2006). This work suggests that these animal-like PLDs in plants work together with PA phosphatase to generate free phosphate and DAG.…”
Section: Chaptermentioning
confidence: 96%
“…The response of membrane lipid composition to Pi starvation essentially may comprise the degradation of phospholipids to release Pi, and the synthesis of glycolipids as nonphosphorus lipids to substitute for those phospholipids (Siebers et al 2015). The role of phospholipase D in the breakdown of PM phospholipids during phosphate deficiency actually was established in oat and thale cress (Andersson et al 2005;Cruz-Ramírez et al 2006). Likewise, the content of SGs as phosphorous-free glycolipids that replace phospholipids is known to increase in the PM as a response to phosphate starvation (Andersson et al 2005).…”
Section: Am-responsive Proteins As Related To Interface Biogenesis Anmentioning
confidence: 99%